Pendampingan Guru Pembelajar pada MGMP Melalui Metode Tutor Sebaya Dengan Pendekatan Andragogi - Artiana, Artiana (Institut Teknologi Pendidikan Indonesia, 2022)
The purpose of writing this article is to (1) optimize the competence of student teachers through the peer tutoring method with an andragogical approach at the Chemistry MGMP